2019
DOI: 10.1017/cjn.2019.334
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Salivary, Platelet and Central Serotonin Levels in Children

Abstract: ABSTRACT:Background:Serotonin (5-HT) is a neurotransmitter synthesized in both the central nervous system (CNS) and in enterochromaffin cells of the gut. 5-HT biosynthesis is separate between the periphery and the CNS. Any observed correlations between centrally and peripherally measured 5-HT remain to be elucidated. Previous efforts have looked for a noninvasive marker of central serotonin, including serotonin in whole blood, plasma, platelets, saliva, and urine; however, results are conflicting.Aim:Finding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…This incompatibility may be partially explained by the fact that most applied psychometric tests covered a wide time frame, which may not be captured by a single time-point assessment of salivary 5-HT. Another explanation can be attributed to the site of origin of 5-HT in human saliva, which appears to be peripheral rather than CNS, as outlined in the majority of relevant studies ( 24 , 25 , 30 , 31 , 69 ). The only studies suggesting the level of 5-HT in saliva reflects its CNS status offer modest support: they either report a relatively low effect size ( 26 ) or examine diurnal fluctuations in salivary 5-HT ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This incompatibility may be partially explained by the fact that most applied psychometric tests covered a wide time frame, which may not be captured by a single time-point assessment of salivary 5-HT. Another explanation can be attributed to the site of origin of 5-HT in human saliva, which appears to be peripheral rather than CNS, as outlined in the majority of relevant studies ( 24 , 25 , 30 , 31 , 69 ). The only studies suggesting the level of 5-HT in saliva reflects its CNS status offer modest support: they either report a relatively low effect size ( 26 ) or examine diurnal fluctuations in salivary 5-HT ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, among many biological fluids, 5-HT is also present in saliva (24)(25)(26)(27). It appears to derive from two 5-HT pools, one associated with the CNS and another with the periphery (28,29), both providing some contribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some papers, serotonin is considered as a stress biomarker, but mainly in blood or urine, where the concentration is higher [ 29 ]. Moreover, Egri et al found out that in children the salivary serotonin levels do not correlate well with plasma levels and Leung et al highlighted that they do not correlate with central serotonin turnover either, making serotonin a non-suitable salivary biomarker for evaluation of serotonergic system functioning [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is true that serotonin has important implications for attention and memory, research has now shown that platelet and salivary levels of serotonin are not accurate reflections of central nervous system serotonin. 2 Stimulant medications were used for children with hyperactivity in the 1970s and remain the first line treatment. They are now thought to work by affecting synaptic levels of dopamine and norepinephrine in the prefrontal cortex, enhancing executive functioning.…”
mentioning
confidence: 99%